Unveiling the enigma: thyroid-like follicular carcinoma of the left kidney - Zafar, Nauman; Iqbal, Saud; Muhammad , Shujah; Nusrat, Nadeem Bin; Rehman, Assad Ur; Imtiaz, Saira (Journal of the Pakistan Medical Association, 2025)
Thyroid-like follicular carcinoma of the kidney (TLFCK) is a rare renal cancer, not aligning with established renal cell carcinoma subtypes. Histologically akin to primary thyroid follicular carcinoma, TLFC poses diagnostic challenges due to absent thyroid immunohistochemistry markers. This case details a 40-year-old army man, previously hypertension-free, presenting with bilateral flank pain and severe haematuria. Imaging revealed a 5.5 × 5 cm calcified lesion in the left kidney, suggestive of renal cell carcinoma (T3aN0Mx). Immunohistochemistry confirmed the diagnosis, with positive Paired box gene 8 (PAX8), Cytokeratin 7 (CK7) and Carbonic anhydrase IX (CAIX) and negative Cluster of differentiation 10 (CD10), Alpha-methyl acyl-CoA racemase (AMACR), Cluster of differentiation 117(CD117), Thyroid transcription factor 1 (TTF1) and thyroglobulin. The tumour was confined to the kidney, with clear margins. Subsequently, signs of metastasis prompted systemic treatment initiation with immunotherapy and tyrosine kinase inhibitors, emphasizing diagnostic intricacies and therapeutic complexities associated with TLFC. Keywords: Thyroid-like follicular carcinoma of the kidney; Renal cell carcinoma; Metastatic follicular carcinoma of the thyroid; WHO classification.